SOLUTION OF THE BOUNDARY VALUE PROBLEM OF A SEMI-INFINITE WAVEGUIDE - Tavbaev J; Saparov B; Kholikulov E (Galaxy International Interdisciplinary Research Journal, 2021)
In this work, more accurate but more complex methods are proposed for propagation of oscillations in cylindrical waveguides. This problem is considered in relation to a specific technical problem of the propagation of elastic vibrations along the drill string arising from a bit working at the bottom of a native well. Information from the signals received at the wellhead in the string can serve as valuable information about the operation of engines at the bottomhole, about the rock near the bottomhole, etc.